1766. Sustained Viral Suppression with Dolutegravir and Boosted Darunavir Dual Therapy Among Highly Treatment-Experienced Individuals. (26th November 2018) - Hawkins, Kellie; Montague, Brian; Rowan, Sarah; Mclees, Margaret; Beum, Robert; Johnson, Steven C; Gardner, Edward
Abstract: Background: The use of antiretroviral (ARV) dual therapy for treatment of HIV is increasing; raltegravir with boosted darunavir (bDRV) is recommended in certain clinical situations in DHHS guidelines. Dolutegravir (DTG) with bDRV has not been widely studied. We sought to determine the effectiveness of DTG/bDRV in treatment experienced patients. Methods: This retrospective cohort study evaluated viral suppression in patients prescribed DTG/bDRV dual therapy within a large urban health system. Data collected included demographics, cumulative ARV exposure, reasons for use, regimen start/stop dates, and viral suppression (HIV-RNA ≤200). Follow-up was defined as the number of days from start of regimen until last HIV-RNA determination on the study regimen. Results: From January 1, 2013 to December 31, 2017, 60 patients received DTG/bDRV dual therapy: 15% were female, median age was 56, 83% were ≥3 class ARV-experienced, and median time since starting ARVs was 20 years. Median follow-up on DTG/bDRV was 444 days (IQR 273–808). Viral suppression was achieved by 59 of 60 (98%) patients at some point on DTG/bDRV. When stratified by baseline viral suppression, 46 of 46 (100%) who had baseline viral suppression maintained viral suppression in comparison to 11 of 14 (79%) without baseline viral suppression (table). The most common reasons for DTG/bDRV were simplification in setting of prior resistance (47%), toxicity reduction (39%), and virologic failure (15%). At study end, 53 of 60 (88%) were still on DTG/bDRV and the most common reason for stopping was drug interactions. Conclusion: In a highly treatment-experienced cohort of patients, DTG/bDRV dual therapy demonstrated sustained rates of viral suppression, even in those who were failing therapy prior to initiating the regimen. Further study of this potent, simple, high-barrier dual class regimen is warranted. Disclosures: S. Rowan, Gilead Sciences: Investigator, Research grant. S. C. Johnson, Viiv Healthcare: Scientific Advisor, Consulting fee.